NOMINATION PROCESSES AND ERGONYM RESEARCH - Xudaybergenova Umida Komildjanovna; Matniyozova Gulizebo Adilbekovna (TADQIQOTLAR, 2026)
Abstract.  This  article  examines  the  linguistic  characteristics  of  the  Russian-speaking  population  and  the  sociocultural  foundations  of  the  nomination  process through  the  prism  of  linguocultural  studies,  one  of  the  most  relevant  fields  of contemporary linguistics. The research provides a comprehensive analysis not only of the principles underlying the formation of onomastic units but also of their relationship with human cognition and national mentality. Furthermore, the communicative and pragmatic  potential  of  ergonyms,  as  well  as  their  role  in  modern  advertising  and marketing systems, are substantiated from a scientific perspective.